2012
DOI: 10.1149/2.006206esl
|View full text |Cite
|
Sign up to set email alerts
|

Study of Chemical Vapor Deposition of Manganese on Porous SiCOH Low-k Dielectrics Using Bis(ethylcyclopentadienyl)manganese

Abstract: MnO/MnSiO 3 -based layers were formed on porous SiCOH low-k dielectrics by Chemical Vapor Deposition (CVD) of Mn from Bisethylcyclopentadienyl manganese. The oxide phase formation is driven by the moisture desorbing from the low-k films. The silicate phase is defined by silanol groups chemisorbed on the low-k surface. The experimental results suggest that formation of thin Mn-based copper diffusion barrier (pore sealing) by CVD is limited to dielectrics having a pore size smaller than the Mn precursor molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…In that case, a couple of major drawbacks arise: i) thicker liners are needed to form pin-holes free barriers, 102,104,105 and ii) the precursor molecules deposit inside the pores before a continuous layer is actually formed on the material surface. 106 Even though the latter could help ensure a good adhesion between the two materials, it should be avoided (or limited to a few nanometers at the interface) to keep the increase in k effective at a minimum. One way to mitigate this penetration phenomena is to pre-treat the dielectric material surface prior to liner deposition.…”
Section: Ecs Journal Of Solid State Science and Technology 4 (1) N30mentioning
confidence: 99%
“…In that case, a couple of major drawbacks arise: i) thicker liners are needed to form pin-holes free barriers, 102,104,105 and ii) the precursor molecules deposit inside the pores before a continuous layer is actually formed on the material surface. 106 Even though the latter could help ensure a good adhesion between the two materials, it should be avoided (or limited to a few nanometers at the interface) to keep the increase in k effective at a minimum. One way to mitigate this penetration phenomena is to pre-treat the dielectric material surface prior to liner deposition.…”
Section: Ecs Journal Of Solid State Science and Technology 4 (1) N30mentioning
confidence: 99%
“…Finally, it is also noted that in contrast to previous work on similar non-treated samples, there is strong evidence of Mn diffusion into the 50% porous substrate after thermal anneal, which has been reported to occur in inter-layer dielectric (ILD) materials that were subject to plasma treatments. 17 …”
Section: Resultsmentioning
confidence: 99%
“…15 Manganese silicate (MnSiO 3 ) barrier layers have been the subject of considerable study due to their reported effectiveness as a barrier to Cu migration and improved Cu adhesion properties compared to other barrier layer candidates. 5,6,16,17 While the majority of studies to date have focused on the formation of MnSiO 3 barrier layers on SiO 2 surfaces, 6,18,19 the growth of the Mn based barrier layers on carbon containing ultra-low dielectric constant (ULK) materials has also been the subject of interest. 7,16,[20][21][22] The formation of effective barrier layers on these surfaces is essential if they are to be adopted by the industry.…”
Section: Introductionmentioning
confidence: 99%
“…Mnbased films (∼1.5 nm thickness) were deposited by chemical vapor deposition 3,4 on a 100 nm thick tetraethylorthosilicate (TEOS)-based BD layer on 300 mm Si wafers and then annealed at ∼450…”
Section: Methodsmentioning
confidence: 99%
“…1 Hence, it has become necessary to replace these Ta/TaN barrier-liner films with thinner and more functional candidate materials. One such candidate is a Mn/Mnbased film since it can form a very thin (∼1 nm) self-forming and excellent Cu diffusion barrier layer of amorphous manganese silicate (MnSi x O y ) at the Mn/low-k (black diamond or SiCOH with k = 2.9 or lower) [1][2][3][4][5][6][7][8][9][10] interface. However, this MnSi x O y layer is not conductive enough and requires a thin conductive liner for the deposition of a Cu seed layer.…”
mentioning
confidence: 99%